Menggali Faktor-Faktor yang Mempengaruhi Transformasi Digital dalam Pelayanan Publik di Kota Banda Aceh dan Kota Jambi - Ali, Chaidir; Wildhani, Annisa Millania; Purwaningsih, Titin (Jurnal Sosioteknologi, 2024)
This research aims to prove the hypothesis regarding the factors that influence digital transformation in public services in of Banda Aceh and Jambi using the TAM framework with the variables usefulness, attitude toward, ease of use, and social influence. This research uses a quantitative descriptive method with data sources from questionnaires distributed via Google Form with 200 respondents and data processing using SMART PLS3 software. The research results show an R-square value of 0.671. It can be concluded that the interpretation of the level of user satisfaction in Banda Aceh and Jambi regarding digital transformation is 67.1%; the r-square is identified in the strong category. Several TAM variables that have a significant influence are ease of use, social influence variables with P values of 0.004 and 0.000, and variables that do not have asignificant effect are usefulness and attitude towards it with P values of 0.511 and 0.056.